PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA MATERI GERAK ROTASI DAN REVOLUSI BUMI PADA KELAS VI MIN 1 NGANJUK - Nova Syahdan Iqbal Fadzilahh; Widi Wulansari; Novi Nitya Santi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by instructional video media on students’ learning outcomes in the topic of Earth’s rotation and revolution among sixth-grade students at MIN 1 Nganjuk. The study was motivated by low student learning outcomes caused by the dominant use of conventional learning models that do not optimally promote student engagement and critical thinking skills. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The research subjects consisted of an experimental class that applied the PBL model assisted by instructional videos and a control class that used conventional learning methods. Data were collected through pretest and posttest instruments that had been tested for validity and reliability. Data analysis was conducted using parametric statistical tests to determine differences in learning outcomes. The results showed that the application of the Problem Based Learning model assisted by instructional video media had a significant effect on improving students’ learning outcomes. The experimental class demonstrated higher learning gains compared to the control class. Therefore, the PBL model assisted by instructional video media is effective and recommended for improving learning outcomes in elementary school science and social studies learning.